Profil Hematologi Darah Indukan Babi Berdasarkan Umur Kebuntingan - Mengga, Indrano Da Pili; Simarmata, Yohanes T.R.M.R; Tophianong, Tarsisius C; Murni, Theresia (Jurnal Veteriner Nusantara, 2024)
Pigs are monogastric livestock and are prolific (many offspring per birth) and have rapid growth. Pregnancy is a physiological phase that can cause metabolic changes in animals resulting in changes in hematology profile. An animal's hematological profile can be observed by knowing the hematological parameters. Blood sampling of pigs will be carried out on a total of 20 pigs with details of 10 one-month pregnant sows and 10 two-month pregnant sows. Blood is taken from the jugular vein using a venoject and placed in an EDTA tube. Then the blood was taken to the laboratory for examination using a hematology analyzer. The results of the hematology examination of one-month pregnant and two-month pregnant sows showed that the number of red blood cells in one-month pregnant sows increased and in two-month pregnant sows there was a slight decrease due to the growing fetus in the two-month gestation period. A decrease in hemoglobin levels in both gestation periods is indicated by a decrease in MCH and MCHC values in each gestation period which then causes iron deficiency anemia due to a lack of iron intake during gestation. Hematocrit values in both gestation periods were not different and showed normal conditions, which made the MCV values in both gestation periods also normal. This indicates that the volume of erythrocytes in the blood is normal. Total leukocytes in one-month and two-month pregnant sows were normal, indicating that at the time of blood collection, sows were not infected with pathogenic agents or under stress.